Costa Rican Drinking-Water Quality Risks Index (IRCACH) - Mora-Alvarado, Darner (2018)
The IRCACH aims is to facilitate the interpretation of the drinking-water analysis within the water supply network in Costa Rica. This index allows to link the consumers’ health risk level with the rejection of drinking-water. Firstly, in order to create the former document, the microbiological and physicochemical parameters established in the national regulation for drinking-water quality were identified and classified according to their implications in water supply network. The parameter classification was operation, aesthetics, pollution indicators, and health risk. Different scores were stablished for each parameter, according to their previous classification. Five risk levels were defined: Very Low Risk, Low Risk, Medium Risk, High Risk, and Very High Risk. Drinking-water quality is considered potable or non-potable depending on the final score. The IRCACH is an integral approach to the analysis interpretation. It can be used for any type of water supply network, i.e. chlorinated or non-chlorinated. The IRCACH is subject to further modifications according to technological advances and scientific knowledge. It proved to be an efficient tool for stablishing the potential health risk with the rejection of drinking-water in Costa Rica.